2007
DOI: 10.1002/jms.1186
|View full text |Cite
|
Sign up to set email alerts
|

In situ diagnostics of the decomposition of silacyclobutane on a hot filament by vacuum ultraviolet laser ionization mass spectrometry

Abstract: The gas-phase reaction products of silacyclobutane (SCB) and 1, 1-dideuterio-silacyclobutane (SCB-d(2)) from a hot-wire chemical vapor deposition (HWCVD) chamber were diagnosed in situ using vacuum ultraviolet (VUV) laser single-photon ionization (SPI) coupled with time-of-flight (TOF) mass spectrometry. The SCB molecule was found to decompose at a filament temperature as low as 900 degrees C. Both Si- (silylene, methylsilylene, and silene) and C-containing (ethene and propene) species were produced from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…Maier et al [33] found that silene was stable only under argon matrix isolation at 10 K and it dimerized to 1,3-disilacyclobutane upon thawing of the matrix at 35 K. In a study of thermal decomposition of 1,1-dimethyl-1-silacyclobutane [34], although kinetic evidence supports the existence of an unstable intermediate, 1,1-dimethyl-1-silene, the only products detected are ethene and 1,1,3,3-tetramethyl-1,3-disilacyclobutane. 1,1-Dimethylsilene, an analog of silene, was found to undergo similar dimerization reactions to yield 1,1,3,3-tetramethyl-1,3-disilacyclobutane: (16) Our study of the hot wire decomposition of silacyclobutane [35] also showed that silene (H 2 Si CH 2 ) was produced, supported by the observation of its dimer signal, 1,3-disilacyclobutane. For the pyrolysis of TMS, 1,1,3,3-tetramethyl-1,3-disilacyclobutane (m/z = 144) [24,29] were previously observed as a product from the analysis by gas chromatography (GC) or GC-MS.…”
Section: Gas-phase Reaction Products From the Hwcvd Reactorsupporting
confidence: 51%
“…Maier et al [33] found that silene was stable only under argon matrix isolation at 10 K and it dimerized to 1,3-disilacyclobutane upon thawing of the matrix at 35 K. In a study of thermal decomposition of 1,1-dimethyl-1-silacyclobutane [34], although kinetic evidence supports the existence of an unstable intermediate, 1,1-dimethyl-1-silene, the only products detected are ethene and 1,1,3,3-tetramethyl-1,3-disilacyclobutane. 1,1-Dimethylsilene, an analog of silene, was found to undergo similar dimerization reactions to yield 1,1,3,3-tetramethyl-1,3-disilacyclobutane: (16) Our study of the hot wire decomposition of silacyclobutane [35] also showed that silene (H 2 Si CH 2 ) was produced, supported by the observation of its dimer signal, 1,3-disilacyclobutane. For the pyrolysis of TMS, 1,1,3,3-tetramethyl-1,3-disilacyclobutane (m/z = 144) [24,29] were previously observed as a product from the analysis by gas chromatography (GC) or GC-MS.…”
Section: Gas-phase Reaction Products From the Hwcvd Reactorsupporting
confidence: 51%
“…A detailed description of the experimental setup using VUV SPI, including the ionization laser source, HWCVD reactor, and the TOF MS, has been reported previously [18,19,26]. Briefly, a HWCVD chamber is connected through a 0.15 mm diameter pinhole to the high-vacuum ionization chamber housing the TOF MS. A tungsten filament (0.5 mm diameter, 10 cm length) is placed in the HWCVD reactor and is resistively heated by a DC power supply.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, single-photon ionization (SPI) using 118 nm vacuum ultraviolet (VUV) laser radiation has proven to be a powerful technique for examining silane chemistry [6]. Our recent studies have shown that VUV SPI also works well with alkylsilane molecular systems in the HWCVD process [18,19]. However, many of the products predicted for the NH 3 and SiH 4 /NH 3 systems, notably H 2 and N 2 , have IPs greater than 10.5 eV.…”
mentioning
confidence: 96%
“…20,21 In brief, a HWCVD reactor, housing a heated tungsten filament, is incorporated by way of a 0.15 mm diameter pinhole into a high-vacuum ionization chamber for the TOF mass spectrometer (R. M. Jordan Inc.). The total pressures in the reactor are maintained at ~ 12 Torr using a mass flow controller (MFC), while those in the ionization chamber are ~ 4.0 x 10 -6 Torr under working conditions.…”
Section: Methodsmentioning
confidence: 99%